IoT-Driven Solutions for Empowering Widows and Safeguarding Women’s Rights in Southern Nigeria - Ayedun, Tosin Olusola; Akpor, Oluwaseyi Abiodun; Alabi, Yetunde Justinah; Olubiyi, Ifeoluwa; Afolalu, Adeniran Sunday (ABUAD Journal of Engineering Research and Development (AJERD), 2025)
The empowerment of women and their autonomy in the areas of social, economic, political, and health is highly necessary. However, some categories of women, like the widows, have been neglected over time when policies that has to do with socio-economic development is being considered in any level of government. Based on this, the study examined how the Rights of women and especially widows are protected. Also, the study further examined the impact of the adoption of Internet of Things technology in ensuring adequate empowerment of women as well of their Rights protection. The findings revealed that training and evaluation of the vulnerable women in this category is important. Also, it was suggested that there must be adequate monitoring of the IoT technology to ensure that is acceptable. More so, training of the widows is very important to ensure their understanding and subsequent improvement in the area of sustainable economy.